Effects of Baduanjin exercise on cancer-related fatigue in patients with prostate cancer treated with androgen deprivation therapy in Shanghai, China: a study protocol for a randomised controlled trial - Yali Li; Yihang Wang; Fei Yao; Yuan Qin; Yifei Xu; Guangxin Guo; Xiruo Xu; Xuanying Zhu; Guangpu Yang (BMJ Open)
Introduction Cancer-related fatigue (CRF) is one of the most common and painful symptoms in patients with prostate cancer (PCa). Moreover, PCa patients who receive the androgen deprivation therapy (ADT) are more likely to develop CRF. Baduanjin exercise has been shown to improve CRF in some cancers. However, such effects have not been verified in patients with PCa treated with the ADT. So, this study was designed as a randomised controlled trial (RCT) to explore the effects of Baduanjin exercise on CRF in PCa patients treated with the ADT.Methods and analysis This study will be a single-centre, assessor and statistician blinded, RCT consisting of a 12 week intervention and 12 week follow-up. Patients with PCa who meet the inclusion criteria will be recruited from Shanghai Hudong Hospital. Participants will be randomly assigned to Baduanjin exercise group (n=42) and the control group (n=42), performing 12 weeks of Baduanjin exercise or reeiving the standard care. The primary outcome will be the clinical effect of Baduanjin exercise on CRF in PCa patients, which will be measured using the Piper Fatigue Self-Assessment (PFS) scale, a multidimensional measure of CRF using three different dimensions: somatic, emotional and cognitive. The secondary outcome will be the clinical effect of the Baduanjin exercise on the patient’s level of fatigue, sleep, depression and life quality at the time, which will be assessed by the Brief Fatigue Inventory (BFI), the Pittsburgh Sleep Quality Index (PSQI), the Beck Depression Inventory (BDI) and the Functional Assessment of Cancer Therapy-Prostate (FACT-P).Ethics and dissemination This study has been approved by Shanghai Hudong Hospital Ethics Committee, Shanghai province (2022 SHHDKY08). The trial results will be submitted to conferences and peer-reviewed journals.Trail registration number ChiCTR2300074293